1974
DOI: 10.1159/000122565
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Localization of LH Releasing Hormone in the Rat Hypothalamus’

Abstract: Luteinizing hormone-releasinghormone (LH-RH), a water soluble decapeptide, was found to be so firmly bound to a subcellular particulate structure in rat hypothalamus that only negligible amounts were solubilized during the homogenization and centrifugation processes. The structures binding LH-RH were localized in the 1.2 Msucrose portion of a discontinuous sucrose gradient. Another neurohormone, vasopressin, was more dispersed and located in the heavier portion of the gradient. Cholinesterase activity was also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1976
1976
1982
1982

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…Such an exclusively synaptosomal distribution is identical to that described for all other neurohormones tested so far (LHRH, Ramirez et al, 1975 ;Shin et al, 1974 ;Taber and Karavolas, 1975 ;TRH, Barnea et al, 1975 ;SRIF, Epelbaum et al, 1976). This similarity suggests that nondopaminergic PIF could be a peptide related to the other neurohormones.…”
supporting
confidence: 81%
“…Such an exclusively synaptosomal distribution is identical to that described for all other neurohormones tested so far (LHRH, Ramirez et al, 1975 ;Shin et al, 1974 ;Taber and Karavolas, 1975 ;TRH, Barnea et al, 1975 ;SRIF, Epelbaum et al, 1976). This similarity suggests that nondopaminergic PIF could be a peptide related to the other neurohormones.…”
supporting
confidence: 81%
“…Also, we cannot disregard the possibility that this route of injection would avoid the pulmonary bed, which has the capacity to inactivate other biologic substances, such as bradykinin, angiotensin, prostaglandins [Ryan et al, 1972], In our experi ments the ovulation-facilitatory activity of the microsomal fraction may be explained by an increase in LH release, by LH potentiation at the ovary level, or by both possibilities. The first possibility must be considered in view of the presence of LH-RH associated to subcellular granules, as was shown by Ishii [1970], Clementi et al [1970], Shin et al [1974] and Taber et al [1975], The last authors reported that, after differential centrifugation, only the crude mitochondrial fraction increased LH release in vitro.…”
Section: Discussionmentioning
confidence: 99%